THE EFFECT OF SYSTEM QUALITY AND INFORMATION QUALITY ON THE SATISFACTION OF USER ENTERPRISE RESOURCE PLANNING (ERP) WITH PERCEIVED USEFULNESS AS MODERATING VARIABLES IN PT PLN (PERSERO) DISTRIBUTION AND CENTER FOR LOAD MANAGEMENT (P3B) SUMATRA UPT MEDAN UPT M - Rahmadani, Tri Yanti (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to test and analyze the effect of System Quality and Information Quality on the End User Satisfaction of Enterprise Resource Planning (ERP) with Perceived Usefulness as a moderating variable and to test and analyze whether the variable System Quality and Information Quality influence simultaneously or partially on the End User Satisfaction Enterprise Resource Planning (ERP) and Perceived Usefulness as moderating variables affect the relationship of System Quality and Information Quality to ERP End User Satisfaction. This type of research is causal research. Data collection is carried out by collecting primary data obtained through the distribution of questionnaires to the employees of PT PLN (Persero) Distribution and Center for Load Management (P3B) UPT Sumatra Medan. The population in this study were all employees of PT PLN (Persero) Distribution and Center for Load Management (P3B) Sumatra UPT Medan. as many as 184 people. The research sample used in this study amounted to 52 people. Hasil Penelitian menunjukkan bahwa parsial Kualitas Sistem mempengaruhi positif signifikan terhadap Kepuasan Pengguna Akhir ERP dan Kualitas Informasi mempengaruhi negatif signifikan terhadap Kepuasan Pengguna Akhir ERP. Secara simultan Kualitas Sistem dan Kualitas Informasi berpengaruh signifikan terhadap Kepuasan Pengguna Akhir ERP. Dan hasil penelitian juga menunjukkan bahwa Kegunaan yang dirasakan bukan merupakan variabelmoderating.